Effect of trypanosome infection on livestock health and production in Togo - Defly, A.; Awuome, K.; Bokovi, K.; D'Ieteren, G.D.M.; Grundler, G.; Handlos, Michael; Itty, P.; Leak, S.G.A.; Maehl, J.H.H.; Mawuena, K.; Morkramer, G.; Nagda, S.M.; et al. (International Livestock Centre for Africa, 1988)
The prevalence, species and intensity of trypanosome parasitaemia in different livestock species, breeds, age groups and management systems are reported from Togo for trypanosotolerant sheep and goats in the Sokode area. The effects of these trypanosome parasitaemias on health and production traits in cattle and sheep are evaluated.